LOPIS RAKSASA PEKALONGAN SEBAGAI SIMBOLISME BIODIVERSITAS KULINER TRADISIONAL DAN KETAHANAN PANGAN: DIPLOMASI BUDAYA DAN PARIWISATA DI TENGAH TANTANGAN INDUSTRIALISASI PANGAN TERHADAP TRADISI LOKAL - Nisaul Mufida; Wasino; Edi Kurniawan; Arghita Aricindy (STKIP Subang, 2025)
Pekalongan lopis raksasa (giant lopis) is a traditional food made from sticky rice that is steamed until solid and wrapped in banana leaves in very large sizes. For Indonesian, food is more than just a biological necessity. It is acomplex intertwining of nature, humanity, and the Creator. Every grain of rice,every piece of side dish, and every blend of spices holds traces of history, philosophical values, andecological knowledge passed down from generation to generation. However, in the modern era, this traditional food system faces enormous challenges. The trend offood industrialization, which encourages monoculture, the use of synthetic chemicals, and flavor standardization, threatens ecological sustainability and cultural diversity. Therefore, it is important to reexamine the richness of the Nusantara food systemof the archipelago. Understanding the philosophy, local wisdom, and potential contained withinis not merely an effort of nostalgia, but a strategic step towardsbuilding food security, food sovereignty, and strengthening national identityon the global stage.